Transporte público metropolitano nas regiões metropolitanas de Londrina e Maringá sob a ótica da mobilidade espacial - Druciaki, Vinícius Polzin [UNESP] (2014)
The cities of Londrina and Maringa reached the category of metropolitan areas in 1998. In essence, the main objective was centered on the management of common problems facing the metropolization process involving nearby towns. One of the early problems for metropolitan areas refers to the mobility of people from a public transportation. In this sense, the only modal that took this demand was the Metropolitan Road Transport (TRM) that, despite the nomenclature, falls into a category of inter-municipal public service, having no relation with the established regions. These were never implemented, thus implying the problem of spatial mobility of people seeking activity sites in the major cities, and who do not have any kind of physical, tariff or temporal integration with the urban transportation of the cities. We understand that social mobility is oriented movement of people and their condition of access to places through a mean of transportation in order to meet their needs in the local activities. Therefore, the spatial mobility in the metropolitan scale in question has no relationship with the institutionalization of these spaces, trampled by the same logic, whether the constant addition of municipalities unrelated to the metropolitan process. Have the logic of spatiality brings elements to differentiate between these spaces with respect to spatial mobility, in which Maringa is most problematic reality because of intense dependence that cities have in relation to the center as well as the network of transport available. In short, given the political dispute (state and local), economic (business segment) in metropolitan areas that today are on paper, to suggest a spatial mobility with equity is a challenge